2009
DOI: 10.1097/pcc.0b013e3181bb2b2b
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of displayed tidal volume in infants and children during dual-controlled ventilation

Abstract: There is an underestimation of delivered tidal volume when compensating for circuit volume loss measured at the ventilator. There is no improvement in measured tidal volume using circuit compensation in small infants and children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…Somewhat improved correlation was found with pediatric circuits: the average measured V T at the endotracheal tube was 73% of that measured at the ventilator. Similar findings have been reported by Castle et al, 40 Chow et al, 41 and Heulitt et al 42 Thus, when determining the actual delivered V T for smaller pediatric patients, the use of a pneumotachometer placed at the endotracheal tube would seem to be the optimal approach. Most newer-generation ventilators include software that is supposed to account for the circuit compliance in calculating the actual delivered V T , 42 but those algorithms have not been systematically studied in the "real life" clinical situation.…”
Section: Tidal Volumesupporting
confidence: 73%
“…Somewhat improved correlation was found with pediatric circuits: the average measured V T at the endotracheal tube was 73% of that measured at the ventilator. Similar findings have been reported by Castle et al, 40 Chow et al, 41 and Heulitt et al 42 Thus, when determining the actual delivered V T for smaller pediatric patients, the use of a pneumotachometer placed at the endotracheal tube would seem to be the optimal approach. Most newer-generation ventilators include software that is supposed to account for the circuit compliance in calculating the actual delivered V T , 42 but those algorithms have not been systematically studied in the "real life" clinical situation.…”
Section: Tidal Volumesupporting
confidence: 73%
“…Although most modern ventilators have built-in software to adjust for mechanical ventilator tubing compliance, VTs measured at the proximal airway with a pneumotachograph are still remarkably different from those measured at the mechanical ventilator. This problem is magnified with infants and smaller children, even when allowing for tubing compliance (61,62), with VTs measured at the ventilator often being considerably higher than those at the endotracheal tube (ETT). In addition, the shape of the expiratory portion of the tidal flowvolume curve is often distorted to an obstructive pattern when acquired in the ventilator rather than at the ETT ( Figure 5), which may lead to incorrect ventilator management choices.…”
Section: Vt Measurementsmentioning
confidence: 99%
“…However, if the inspiratory flow is not zero when inspiration ends (Fig. 2), we cannot be sure that the volume of air which left the ventilator has reached the alveoli [13]. We showed in our experiment that this phenomenon would account for the undelivered volume that we observed with PCV and PRVCV modes.…”
Section: Discussionmentioning
confidence: 67%
“…This difference was lower than in PCV and PRVCV, and it would be due to the circuit volume loss because of circuit compliance. It has been demonstrated that the internal computer software of the ventilator to compensate for circuit volume loss is not effective, mainly when TV is small [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation